The Combined Use of Lachancea thermotolerans and Lactiplantibacillus plantarum (former Lactobacillus plantarum) in Wine Technology - Ángel Urbina; Fernando Calderón; Santiago Benito (Foods, 2021)
Most commercialized red wines are produced through alcoholic fermentation performed by yeasts of the Saccharomyces genus, and a second fermentation performed by lactic bacteria of the Oenococus oeni species once the first is completely finished. However, the classical process can suffer complications, of which the risks can increase in grape juices with high contents of sugar and pH. Due to climate change, these situations are becoming more common in the winemaking industry. The main risks in those scenarios are alcoholic-fermentation stops or sluggish and undesirable bacteria development while alcoholic fermentation is not finished yet and wine still contains residual sugars. The study propose a novel alternative that offers a solution or reduces the risk of those scenarios while increasing acidity, which is another serious problem of warm viticulture regions. The alternative consists of the combined use of Lachancea thermotolerans to reduce the pH of musts that suffer from a lack of acidity, Lactiplantibacillus plantarum (formerly Lactobacillus plantarum) to achieve malic acid stability during the first stages of alcoholic fermentation, and Saccharomyces bayanus to complete the alcoholic fermentation in difficult wines of high potential alcohol degree of over 15% (v/v). The new proposed biotechnology produced wines with higher final concentrations in lactic acid, glycerol, color intensity, ethyl lactate and 2-phenyl ethyl acetate in 2.39 g/L, 0.52 g/L, 21%, 48% and 37% respectively than the classical methodology where Saccharomyces genus performs alcoholic fermentation and later Oenococus oeni performs malolactic fermentation. Additionally, the new alternative produced wines with lower concentration in ethanol, pH, acetic acid, ethyl acetate, diacetyl and 1-propanol in 0.37% (v/v), 0.26, 0.08 g/L, 22%, 69% and 28% respectively than the classic method.